Kecerdasan Emosional, Kompensasi dan Kompetensi terhadap Komitmen Pegawai pada Dinas Pendidikan Kabupaten Ciamis - Ayu Sri Mardiana; Ading Rahman Sukmara; Enas Enas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The study focuses on the Influence of Emotional Intelligence, Compensation and Competence on Employee Commitment (Case Study of the Ciamis Regency Education Office) the problems that arise in the company are caused by this. The problems faced in this study include: 1) How does emotional intelligence affect employee commitment at the Ciamis Regency Education Office? 2) How is financing for employee commitment at the Ciamis Regency Education Office? 3) How is competence related to employee commitment at the Ciamis Regency Education Office? 4) How does emotional intelligence, competence and competence affect employee commitment at the Ciamis Regency Education Office? The objectives of this study are 1). To find out how emotional intelligence affects employee commitment at the Ciamis Regency Education Office, 2). To find out how compensation affects employee commitment at the Ciamis Regency Education Office; 3). To find out how competence affects employee commitment at the Ciamis Regency Education Office, 4) To find out how emotional intelligence, competence and competence affect employee commitment at the Ciamis Regency Education Office. The study uses a descriptive design analysis method with a survey technique. To process the data used Correlation Coefficient Analysis, Multiple Correlation Coefficient, Determination Coefficient. Emotional intelligence towards employee commitment at the Ciamis Regency Education Office with the results of multiple regression tests for the emotional intelligence variable obtained a regression coefficient or β1 of 0.893 which has a positive relationship level to employee performance. This is in line with the results of the hypothesis test, it is known that the correlation can be said to be significant if the Sig. Value <a (alpa) the calculation results above with a (alpa) = 5% or 0.05 while the Sig. value for the emotional intelligence variable (X1) is 0.000. So from the results of the calculation it turns out that emotional intelligence has a positive effect on employee commitment.